ANALISIS KEBUTUHAN BAHAN BACAAN MULTIMODAL BERBASIS KEARIFAN LOKAL UNTUK SISWA SMA HOLY KIDS BERSINAR MEDAN - Elisabet Maibang; Liana Siburian; Candra Ronitua Gultom; Losten Tamba; Dairi Sapta Rindu Simanjuntak; Khatrina Uli Sitanggang; Riwando Aritonang; Selomitha Br Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The availability of reading materials that suit the characteristics of students is an important factor in supporting Indonesian language learning. However, various findings in schools show that students still experience difficulties in understanding long reading and have not received reading material that is able to attract their attention optimally. This research aims to analyze the need for multimodal reading materials based on local wisdom for high school students. The research uses a descriptive approach by utilizing the analysis stage in the ADDIE development model. The research subjects consisted of 30 class XII students at Holy Kids Bersinar Medan Private High School. Data was collected through reading comprehension tests, reading interest questionnaires, observations, and interviews with deputy principals. Quantitative data was analyzed descriptively using percentages and averages, while qualitative data was analyzed through data reduction, data presentation, and drawing conclusions. The research results showed that only 3 students (10%) reached the Minimum Completeness Criteria (KKM) on the long article comprehension test, while 27 students (90%) had not reached the KKM. The results of the reading interest questionnaire obtained an average score of 42.33 or 66.14%, which is included in the medium category. Apart from that, the observation results show that there are symptoms of reading fatigue, which is characterized by students' boredom when reading long texts. The interview results also show that the limited variety of reading materials and literacy facilities are factors that influence students' reading activities. Based on these findings, students need reading material that combines multimodal elements and local wisdom to make it more interesting, contextual, and in line with Indonesian language learning needs.